Scalability of Voice Traffic in OLSR and AODV Mesh: Preliminary Experiments - Om, Shree (International Journal of Computer Sciences and Engineering, 2025)
Community Wireless Mesh Networks (WMNs) have emerged as a cost-effective ‘last-mile’ solution to network services in rural low-income regions primarily located in Sub-Saharan Africa and Developing Asia. However, researchers have often criticized the WMNs for experiencing degraded Quality of Service (QoS), particularly in terms of latency, jitter, and packet loss, as network size and number of users increase. This study investigates the performance of latency, jitter, and packet loss in a multi-hop WMN environment using QoS sensitive voice traffic and two widely used routing protocols - Optimized Link State Routing (OLSR) and Ad hoc On-Demand Distance Vector (AODV) – to determine the most suitable mesh routing protocol for future scalability experiments. Given the strict QoS requirements of voice traffic, the research assumes that a WMN that scales well under voice traffic has the potential to scale well for a broader range of network applications. Using Network Simulator-3 (NS-3), one-way latency, jitter, and packet loss percentage (PL%) were evaluated for up to five simultaneous VoIP calls over a 9-hop WMN topology. The results indicate that while both OLSR and AODV maintained packet loss below 1%, OLSR consistently outperformed AODV in terms of lower latency and jitter. The findings suggest that OLSR is better suited for supporting real-time voice applications in WMNs. Future work will extend this research to analyse WMN scalability under video traffic, explore alternative network topologies (e.g., grid-based WMNs), integrate mobile phones, and evaluating the impact of MIMO routers and varying signal strengths. This study contributes to the ongoing efforts to quantify WMN scalability so that they can be optimally deployed as a community-driven Internet infrastructure.